Bioplastics based Crystalline Cellulose from Bamboo Fibre, Poly (Lactic Acid) and Poly (Butylene Succinate) Nanocomposites using Acid Hydrolysis Method - NURUL JANNAH MD SALLEH; Nasrul Fikry Che Pa (Progress in Engineering Application and Technology, 2026)
The synthesis and characterisation of bioplastic nanocomposites reinforced with crystalline cellulose (CC) derived from bamboo fibre using the acid hydrolysis process is the main goal of this work. The extracted CC was surface modified by acetylation and added to a combination of polylactic acid (PLA) and polybutylene succinate (PBS) to enhance compatibility with the polymer matrix. The effects of filler loading, surface modification, and CC extraction on the composites’ chemical, morphological, thermal, and mechanical performance were examined. Successful CC acetylation was validated by Fourier Transform Infrared (FTIR) analysis, which showed decreased hydroxyl (–OH) intensity about 3330 cm⁻¹ and ester carbonyl (C=O) peaks at about 1740 cm⁻¹, suggesting improved hydrophobicity and interfacial compatibility. Acetylated, bleached CC demonstrated a rod-like shape with particle sizes under 200 nm and consistent dispersion within the PLA/PBS matrix at low filler loading, according to Field Emission Scanning Electron Microscopy (FESEM). The nucleating impact of CC in the polymer mix was confirmed by Differential Scanning Calorimetry (DSC) findings, which showed an increase in crystallinity from 21.6% to 29.4%. Thermogravimetric analysis (TGA) revealed decreased weight loss at 600 °C and increased thermal stability, with the maximum degradation temperature rising from 348 °C to 371 °C. The composite containing 0.5 phr acetylated, bleached CC showed the most promising tensile performance due to its superior chemical compatibility, higher crystallinity, enhanced thermal stability, and homogeneous filler dispersion, despite sample constraints limiting quantitative tensile testing. In polymer composites, these features are known to limit stress concentration and encourage effective stress transmission. Overall, the results show that PLA/PBS bioplastics may be effectively reinforced with acetylated bamboo-derived CC at low loading, underscoring its potential for sustainable packaging applications.